2017
DOI: 10.1177/1087054717707580
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of the ADHD Cognitions Scale for Adults

Abstract: The clinical literature on ADHD in adults suggests that “overly positive” or optimistic cognitions may contribute to impairment and failure to use self-regulation skills in this population, yet the research literature on this topic is limited. We developed the ADHD Cognitions Scale (ACS), a brief self-report measure of ADHD-related thoughts, and evaluated its psychometric properties in two large community samples (Ns = 262, 304). The measure demonstrated a one-factor solution that replicated in the second samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Existing studies have reported that adults with ADHD endorse significantly more negative or maladaptive thoughts than control groups, both in cases of ADHD with and without comorbid diagnoses (Knouse, Zvorsky, & Safren, 2013; Mitchell, Benson, Knouse, Kimbrel, & Anastopoulous, 2013; Strohmeier, Rosenfield, DiTomasso, & Ramsay, 2016). A recent empirically based adult ADHD cognition scale is comprised of maladaptive positive thoughts about tasks that function as rationalizations for deferring a task, consistent with the observation of hedging themes in the user language in the current study (Knouse, Mitchell, Kimbrel, & Anastopoulos, 2017).…”
Section: Discussionsupporting
confidence: 73%
“…Existing studies have reported that adults with ADHD endorse significantly more negative or maladaptive thoughts than control groups, both in cases of ADHD with and without comorbid diagnoses (Knouse, Zvorsky, & Safren, 2013; Mitchell, Benson, Knouse, Kimbrel, & Anastopoulous, 2013; Strohmeier, Rosenfield, DiTomasso, & Ramsay, 2016). A recent empirically based adult ADHD cognition scale is comprised of maladaptive positive thoughts about tasks that function as rationalizations for deferring a task, consistent with the observation of hedging themes in the user language in the current study (Knouse, Mitchell, Kimbrel, & Anastopoulos, 2017).…”
Section: Discussionsupporting
confidence: 73%
“…In addition, a number of validity checks were incorporated to ensure the validity of the responses. The use of MTurk has been shown to be useful in initial scale development (e.g., Knouse, Mitchell, Kimbrel, & Anastopoulos, 2017).…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…This led Solanto et al (2008) to suggest that psychopharmacological treatment alone may not be sufficient to improve skill deficits that often facilitate functional impairment (e.g., time management, difficulties planning, disorganization, procrastination, incomplete or inaccurate work). Thus, psychosocial treatments have also been developed as a possible means to reduce functional impairment and symptom expression, with some success (Hesslinger et al, 2002; Knouse et al, 2017; Safren et al, 2005; Solanto et al, 2008; Solanto et al, 2010; Stevenson, Whitmont, Bornholt, Livesey, & Stevenson, 2002; Weinstein, 1994; Wilens et al, 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding executive function skills related to time management, Imura et al (2016) reported that time management in real life is affected by factors such as the estimation of the time required for tasks, utilization of time for setting goals, priorities, planning, and procrastination. Knouse et al (2017) likewise recounted that “overly positive” or optimistic cognitions of ADHD in adults may contribute to impairment of time management. Therefore, to improve time management of adults with ADHD, it was assumed that it would be necessary to learn not only how to supplement time processing problems, but also how to estimate time, utilize time including planning, and prevent procrastination.…”
Section: Introductionmentioning
confidence: 99%